THE SOURCE OF CALCIUM IN WET ATMOSPHERIC DEPOSITS: CA-SR ISOTOPE EVIDENCE - Schmitt A.D.; Stille P. (My University, 2005)
Tracing the origin of calcium in wet atmospheric deposits is important for environmental studies since it is a dominant acid neutralising cation and an essential nutrient. Here we present the first calcium isotope ratio measurements for rain and snow. Samples from northeastern and southern locations (France, Switzerland, Luxembourg, California and Japan) suggest a carbonate origin. Only at a local scale in a forested watershed (Vosges mountains, France) the Ca isotopic compositions of rainwater indicate that the rainwater becomes admixed with throughfall solution, which is a mixing product of Ca from dissolved atmospheric dust particles and leave excretions. If this proves to be widely true, the contribution of Ca from the canopy could be very important for the neutralisation of acid rain and of the corresponding soil system in forested watersheds. In such cases Ca and Sr cycles are decoupled in the lower atmosphere. In contrast to Sr isotopes, Ca isotopes can be applied to tracing processes occurring in the biosphere.